The Relationship between Leg Muscle Explosive Power and Swimming Speed of 50-Meter Breaststroke Sprint Athlete - Jocellyn, J; Lesmana, Syahmirza Indra; Amir, Trisia Lusiana; Wahyuddin, W (Universitas Muhammadiyah Surakarta, 2022)
Objective: is to determine the relationship between the explosive power of the leg muscles and the swimming speed of the 50m breaststroke sprint athlete aged. Methods: this research is a non-experimental research in the form of a correlation study to analyze the relationship between leg muscle explosive power and swimming speed of 50m breaststroke sprint athletes. There are 23 swimmers as the samples from Tumit Mitra Bangsa Swimming Association with an age range of 12-17 years taken with purposive sampling technique. The measurements taken were leg muscle explosive power with vertical jumps and swimming speed by mathematical calculation of the division of the pool distance (50m) with a record of the swimmer's time measured using a stopwatch. Result: the correlation test with the Spearman rank correlation coefficient showed a significant relationship with a value of p = 0.001 (p <0.05) with a very strong relationship (r = 0.997), which means greater explosive power of the leg muscles increases the swimming speed of the 50m breaststroke sprint athlete. The average with a standard deviation of leg muscle explosive power is 45.85 ± 5.99 and at swimming speed is 1.07 ± 0.15. Conclusions: there is a significant relationship between leg muscle explosive power and 50m breaststroke swimming speed.